2011
DOI: 10.1108/13665621111117215
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning factors of an organizational learning culture

Abstract: PurposeThe aim of this study is to assess the relationship between some variables (organizational structure, organizational dimension and age, human resource characteristics, the external environment, strategy and quality) and organizational learning culture and evaluate the way they interact with this kind of culture.Design/methodology/approachData were collected from 107 Portuguese companies, where a total of 1,122 workers were asked about learning culture through a questionnaire. Data about the other organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 49 publications
8
61
0
2
Order By: Relevance
“…Moreover, IT potential to act as OL enabler is mostly lost, because it constantly faces barriers imposed by the high hierarchy and bureaucracy. Such findings are actually in accordance with the empirical studies of Martínez-León and Martínez-García (2011) and Rebelo and Gomes (2011) that found that with the flatter organizational structure the OL processes become more open and vice versa.…”
Section: Organizational Structure and Organizational Learningsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, IT potential to act as OL enabler is mostly lost, because it constantly faces barriers imposed by the high hierarchy and bureaucracy. Such findings are actually in accordance with the empirical studies of Martínez-León and Martínez-García (2011) and Rebelo and Gomes (2011) that found that with the flatter organizational structure the OL processes become more open and vice versa.…”
Section: Organizational Structure and Organizational Learningsupporting
confidence: 92%
“…The findings in some studies (Ashton, 2004;Martínez-León and Martínez-García, 2011;Rebelo and Gomes, 2011) indicate that OL development involves flatter organizational structures with open communication channels and circulation of information and that relies on management that practices the right balance of control and authority. As the part of the organizational infrastructure, the role of IT systems in the processes of OL is also very important, particularly when it comes to the transfer of explicit knowledge (Alavi and Leidner, 2001).…”
Section: Organizational Learning and Organizational Factorsmentioning
confidence: 99%
“…In outsourcing scenarios, different cultures and organizations are mixed and factors considered critical for the effectiveness of workplace learning (e.g. organizational learning culture (Rebelo and Duarte Gomes, 2011)) vary in a considerable amount. In IT picture, there are several works reporting that software engineers did not find formal courses efficient to acquire application-domain knowledge and most employees learn how to solve a problem at hand informally from peers ( Johnson and Senges, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Li et al [59] study showed a positive relationship among OC, organizational performance and learning. As well as, Rebelo and Duarte Gomes [88] mention for strengthening organization success is the result of OC orientation towards organizational learning. This result is consistent with a previous study conducted by López et al [89] to measure organizational Performance in Spanish factories, which produced a positive relationship between OC and organizational learning with performance.…”
Section: Moderating Effect Of Organizational Culture Between Organizamentioning
confidence: 99%